Estudo do gene da fotoliase de tripanossomatídeos: expressão heteróloga do gene de Trypanosoma brucei EM Trypanosoma cruzi - Egidio Paulo Francisco Nhavene (2014)
The Trypanosoma cruzi and Trypanosoma brucei are the protozoa parasites that cause African and American trypanosomiasis. Both are characterized by the presence of a single flagellum, a kinetoplast, which is elongated and single mitochondria that occupies much of the cell volume concatenated into a network of DNA. These parasites also exhibit homogeneous morphological characteristics, defined according to the position of the kinetoplast in relation to the nucleus and the presence or absence of flagellum and undulating membrane. Inside of the invertebrates insect host they occur as metacyclic trypomastigotes and epimastigotes forms, while inside of the mammiferous vertebrates hosts may be found as amastigote and bloodstream trypomastigote forms. The genome sequencing of these parasites showed the existence of genes that is related to DNA maintenance such as direct reversal of base changes by dimethylation processes or by the action of photolyases and dioxygenases or by removal of incorrectly incorporated bases repairing by MMR, removal of bulky damage by NER and removal of damage bases by BER, repair of SSBs and repair of DSB by HR. Among the repair pathways described above, Photoreactivation is a direct repair mechanism that catalyzes the reversion of pyrimidine dimers in monomers. There are several kinds of photolyases according to their substrate specificity. Another mechanism to repair UV-induced lesions is NER, which can be divided into two major pathways: Global Genome Repair and the Transcription Coupled Repair. The T. brucei has two photolyase genes, a nuclear photolyase gene which encodes a single stranded photolyase or cryptochromes DASH and a mitochondrial photolyase gene which encodes a CPD photolyase class I. However, the T. cruzi has only the mitochondrial photolyase gene which encodes a single stranded photolyase or cryptochromes DASH. In the present work we studied the effect of UV radiation in wild-type cells, T. cruzi strains heterologously expressing the T. brucei nuclear photolyase gene, T. cruzi CSB single-knockout cells and CSB single-knockout T. cruzi strains heterologously expressing the T. brucei nuclear photolyase gene. The results show that T. cruzi heterologously photolyase the nuclear gene of T. brucei are more resistant to UV irradiation than the wild type. There was not the same activity in T. cruzi CSB single-knockout strains heterologously expressing the T. brucei nuclear photolyase gene. Another important fact is that the wild-type cells, when placed for 60 min under white light after treatment with UV light, do not return to growth. These data suggest that photolyase.